Faktor-Faktor Yang Mempengaruhi Struktur Modal Perusahaan Yang Terdaftar di Jakarta Islamic Index Periode 2013-2017 - Nisaaul Jamil; Atina Shofawati (Jurnal Ekonomi Syariah Teori dan Terapan, 2019)
This study aims to determine the effect of profitability, liquidity and firm size on the capital structure of companies listed in the Jakarta Islamic Index Period 2013-2017. The research method used is quantitative approach. The data in this research is panel data. The analysis technique in this research is multiple linear regression. The results showed that simultaneously profitability, liquidity and firm size have a significant influence on capital structure. Profitability partially has a significant influence on capital structure. Liquidity and firm size have no significant effect on capital structure. The results of this study are expected to expand the knowledge that is important for practitioners and academics.Keywords: Profitability, Liquidity, Firm Size, Capital StructureREFERENCESBaltagi, B.H. 2001. Econometric Analysis of Panel Data. Second Edition. West Sussex. John Wiley & Sons, LTD.Brigham, Eugene F. Dan Joel F. Houston. 2001. Manajemen Keuangan. Jakarta : Erlangga.Buhari, Andi. Noer Azam Achsani, Mangara Tambunan, Tubagus NurAhmad Maulana. 2016. The Differences of Capital Structure Based OnOwnership, Variance, andCorrelation : Venture Capital Firms in Indonesia. International Journal of Science : Basic and AppliedResearch (IJSBAR) Vol. 25, No. 3, pp 128-141.Bursa Efek Indonesia. 2018. Laporan Tahunan (Online). (http://www.idx.co.id/id-id/beranda/perusahaantercatat/laporankeuangandantahunan.aspx.) diakses 07 Mei 2018.Istiqomah, Noor. 2011. Determinan Struktur Modal Perusahaan Manufaktur Yang Terdaftar Di Bursa EfekIndonesia (BEI) Periode 2007-2009. Skripsi. Surabaya Fakultas Ekonomi dan Bisnis Universitas Airlangga.Karadenis, Erdinc. Serkan Yyilmaz Kandir, Mehmet Balcilar, Yildirim Beyazid Onal. 2009. Determinants Of CapitalStructure : Evidences From Turkish Lodging Companies. International Journal Of Contemporary HospitalityManagement. Vol. 21, Issue : 5, pp. 594-609.Kasmir. 2013. Analisis Laporan Keuangan. Jakarta : PT. Raja Grafindo Persada.Manulung. 2005. Pengantar Manajemen Keuangan. Yogyakarta:ANDI.Mouamer, Faris M. Abu. 2011. The Determinant of Capital Structure of Palestine-Listed Companies. The JournalRisk Finance. Vol. 12, Issue : 3, pp. 226-241.Mufaidah. 2015. Pengaruh Struktur Modal Terhadap Harga Saham Perusahaan Pada Jakarta Islamic IndexPeriode 2009-2013. Skripsi. Surabaya Fakultas Ekonomi dan Bisnis Universitas Airlangga.Permatasari, Vina Septiana. 2015. Pengaruh Ukuran Perusahaan, Profitabilitas, dan Ukuran Dewan DireksiTerhadap Index Islamic Social Reporting Pada Perusahaan Yang Terdaftar Dalam Jakarta Islamic IndexTahun 2011-2013. Surabaya Fakultas Ekonomi dan Bisnis Universitas Airlangga.Prasetyo, Bambang dan Lina Miftahul Jannah. 2008. Metode Penelitian Kuantitatif. Jakarta: PT RajaGrafindoPersada.Purwidyastuti, Rifka Catur. 2010. Determinan Struktur Modal (Studi Pada Perusahaan Perbankan Yang Tedaftar DiBEI 2004-2007). Skripsi. Surabaya Fakultas Ekonomi Dan Bisnis Universitas Airlangga.Ratri, Annisa Mega dan Ari Christianti. 2017. Pengaruh Size, Likuiditas, Profitabilitas, Resiko Bisnis, danPertumbuhan Penjualan terhadap Struktur Modal Pada Sektor Industri Properti. JRMB Vol. 12, No. 1.Riyanto, Bambang. 2013. Dasar-dasar Pembelanjaan Perusahaan. Edisi Keempat. Yogyakarta: BPFE.Sheikh, Nadeem Ahmed & Zongjun Wang. 2011. “Determinants of Capital Structure: An Empirical Study of Firmsin Manufacturing Industry Of Pakistan”, Managerial Finance, Vol. 37, Issue: 2, pp. 117-133.Syamsiyah. 2014. “Analisis Struktur Modal Perusahaan yang Terdaftar di Jakarta Islamic Index (JII) Tahun 2009-2013”, Jurnal Iqtishadia. Vol. 7, No. 1.Umar, Husein. 2011. Metode Penelitian untuk Skripsi dan Tesis Bisnis. Jakarta: Rajawali Press.Weston, J. Fred & Eugene F. Brigham. 1990. Dasar-dasar Manajemen Keuangan. Jakarta: Erlangga.Weston, J. Fred & Thomas E. Copeland. 1996. Manajemen Keuangan. Jakarta: Erlangga